Perencanaan Strategis SI dan TI Pada Aplikasi Gudang Menggunakan Metode Ward and Peppard Pada CV.Ribka Furniture - Edy Kurniawan; Yani Rahardja; Penidas Fiodinggo Tanaem (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
CV. Ribka Furniture is a company engaged in furniture. Because the development of Information Systems and Information Technology (IS / IT) to support business processes and fulfillment of the vision and mission, a good plan is needed. In this study, it focuses on the warehouse management system in which there is no good warehouse application in accordance with the exact conditions. Regarding the data method, this research is a qualitative descriptive study using the Ward and Peppard method. Which includes SWOT analysis, Value Chain analysis, PEST analysis, application mapping analysis using the McFarlan Strategic Grid approach and analysis of Information Systems Proposals. This study will produce a recommendation form a portfolio of business process development applications in the Warehouse section into a Web-based form where all the processes in it are integrated into one. So that the warehouse part business process can be done in an application which can support the use of paper and facilitate business processes in the warehouse.